Suppression of Vimentin Phosphorylation by the Avian Reovirus p17 through Inhibition of CDK1 and Plk1 Impacting the G2/M Phase of the Cell Cycle - Chiu, Hung-Chuan; Huang, Wei-Ru; Liao, Tsai-Ling; Wu, Hung-Yi; Munir, Muhammad; Shih, Wing-Ling; Liu, Hung-Jen (PloS one, 2016)
The p17 protein of avian reovirus (ARV) causes cell cycle retardation in a variety of cell lines; however, the underlying mechanism(s) by which p17 regulates the cell cycle remains largely unknown. We demonstrate for the first time that p17 interacts with CDK1 and vimentin as revealed by reciprocal co-immunoprecipitation and GST pull-down assays. Both in vitro and in vivo studies indicated that direct interaction of p17 and CDK1/vimentin was mapped within the amino terminus (aa 1-60) of p17 and central region (aa 27-118) of CDK1/vimentin. Furthermore, p17 was found to occupy the Plk1-binding site within the vimentin, thereby blocking Plk1 recruitment to CDK1-induced vimentin phosphorylation at Ser 56. Interaction of p17 to CDK1 or vimentin interferes with CDK1-catalyzed phosphorylation of vimentin at Ser 56 and subsequently vimentin phosphorylation at Ser 82 by Plk1. Furthermore, we have identified upstream signaling pathways and cellular factor(s) targeted by p17 and found that p17 regulates inhibitory phosphorylation of CDK1 and blocks vimentin phosphorylation at Ser 56 and Ser 82. The p17-mediated inactivation of CDK1 is dependent on several mechanisms, which include direct interaction with CDK1, p17-mediated suppression of Plk1 by activating the Tpr/p53 and ATM/Chk1/PP2A pathways, and p17-mediated cdc25C degradation via an ubiquitin- proteasome pathway. Additionally, depletion of p53 with a shRNA as well as inhibition of ATM and vimentin by inhibitors diminished virus yield while Tpr and CDK1 knockdown increased virus yield. Taken together, results demonstrate that p17 suppresses both CDK1 and Plk1functions, disrupts vimentin phosphorylation, causes G2/M cell cycle arrest and thus benefits virus replication.